Peningkatan Daya Panel Surya Dengan Konsentrator Cahaya dari Bahan Aluminium Foil - Parlin Siagian; Hermansyah Alam; Muhammad Fahreza; Ridho Anggu Frasasti (Jurnal Serambi Engineering, 2024)
Solar Power Plant is a new renewable energy source that can be utilized and is very accessible because it uses sunlight as the main medium of generation. Sunlight is expected to shine on the solar panel with a breakthrough using an aluminum foil reflector. Aluminum foil that provides reflection of sunlight can increase the output efficiency of solar panels. To get the productivity of electricity generated by the panel, maximum sunlight is needed on the surface. Reflectors can increase the intensity of sunlight with less heat generated. By using aluminum foil, the sunlight will be directed to the solar panel thus increasing the output power produced. The angle and tilt of the reflector will be adjusted to the position of the solar panel. The reflection of the aluminum foil has an effect on the intensity of light received by the solar panel and an increase in output power of 2-5%.